Two-Year Caries Clinical Study of the Efficacy of Novel Dentifrices Containing 1.5% Arginine, an Insoluble Calcium Compound and 1,450 ppm Fluoride - Kraivaphan, P.; Amornchat, C.; Triratana, T.; Mateo, L.R.; Ellwood, R.; Cummins, D.; DeVizio, W.; Zhang, Y.-P. (Caries research, 2013)
A 2-year double-blind randomized three-treatment controlled parallel-group clinical study compared the anti-caries efficacy of two dentifrices containing 1.5% arginine, an insoluble calcium compound (di-calcium phosphate or calcium carbonate) and 1,450 ppm fluoride (F), as sodium monofluorophosphate, to a control dentifrice containing 1,450 ppm F, as sodium fluoride, in a silica base. The 6,000 participants were from Bangkok, Thailand and aged 6-12 years initially. They were instructed to brush twice daily, in the morning and evening, with their randomly assigned dentifrice. Three trained and calibrated dentists examined the children at baseline and after 1 and 2 years using the National Institute of Dental Research Diagnostic Procedures and Criteria. The number of decayed, missing and filled teeth (DMFT) and surfaces (DMFS) for the three study groups were very similar at baseline, with no statistically significant differences among groups. After 1 year, there were no statistically significant differences in caries increments among the three groups. After 2 years, the two groups using the dentifrices containing 1.5% arginine, an insoluble calcium compound and 1,450 ppm F had statistically significantly (p < 0.02) lower DMFT increments (21.0 and 17.7% reductions, respectively) and DMFS increments (16.5 and 16.5%) compared to the control dentifrice. The differences between the two groups using the new dentifrices were not statistically significant. The results of this pivotal clinical study support the conclusion that dentifrices containing 1.5% arginine, an insoluble calcium compound and 1,450 ppm F provide significantly greater protection against caries lesion cavitation, in a low to moderate caries risk population, than dentifrices containing 1,450 ppm F alone.